Contaminated soil 2000 proceedings of the Seventh International FZK/TNO Conference on Contaminated Soil, 18-22 September 2000, Leipzig, Germany. (Thomas Telford, 2000)
This volume presents the proceedings of ConSoil 2000, the 7th International FZK/TNO conference on contaminated soil (in co-operation with UFZ Leipzig-Halle). This series of conferences focuses on policies, research and development, regulations practical implementation and experiences related to contaminated sites.